EFFECTS OF ICT ADVANCEMENT ON HUMAN RESOURCE MANAGEMENT IN SELECTED ENTERPRISES IN ABIA STATE, NIGERIA - M.E, EDEJA, SUNDAY; PASCHAL C, ANYANWU,; T.S., NWIGBO (IJRDO - Journal of Business Management, 2017)
the focus of this paper is to examine the effects of ICT advancement on human resource management in selected enterprises in Abia state, Nigeria The study took a descriptive survey approach. Data was sourced from a five point likert scale questionnaire administered on a sample of 219 respondents who were drawn from a population of 240 human resource management staff of twenty five selected firms in Abia state. The data gathered were analyzed with Mann-Whitney (U) test using the 20.0 version of statistical package for social sciences (SPSS). It was discovered that as changes in ICT occurs, it drives a change in the function and process of HRM. The paper therefore concludes that ICT has significant effect in the integration and performance of operational, relational and transformational human resource management; therefore, top management in organizations in Abia state should embrace the ICT option in their pursuit for effective and efficient human resource management. It was recommended among others that; organizations should have home e-HRM programmes that addresses their peculiar needs instead of adopting any kind of e-HRM which does not confer strategic and cost benefits to the organization